Review on life cycle analysis (LCA) studies of reusable plastic crates for fruit and vegetables - Si Gao; Juanjuan Yao; Xuchen Zhao; Pinqiao Ren; Mathias Gustavsson; Chunfei Wu (International Journal of Sustainable Engineering)
Fruits and vegetables require proper packaging to ensure safe transports from farm to shops and retailers. Poor packaging may result in food losses or waste by reduced shelf life. The production and use of the packaging material generates GHG emissions and so does transports and disposal of packaging. The use of reusable plastic crates (RPC), instead of disposable boxes, was found to be a feasible solution in reducing waste and environmental impacts throughout the lifecycle of secondary and tertiary packaging. The aim of this study is to provide a review of Life Cycle Analysis (LCA) of RPC systems for fruits and vegetables under different scenarios. The paper focuses LCA studies of RPC systems for fruits and vegetables from cradle to grave. It aims to review the key designs of the LCA and identify the system boundary, functional unit and main findings. The review presents global warming potential (GWP) results associated with the use of reusable plastic crates, which were observed to be 65–628 g CO2 eq. per cycle of crate during service life. Meanwhile, cross-cutting issues are discussed which can reduce food losses as part of transportation, providing additional benefits for this system as compared to conventional crate solutions.